Relationships between McGregor’s X and Y theory, compensation form, and job satisfaction - Madero-Gómez, Sergio M. (Universidad Autónoma de Tamaulipas, 2018)
When Douglas McGregor started working on the human side of businesses, the way of thinking and managing was very different from the present time. The goal of this research is to determine the validity and reliability of a survey commonly used in the research for Anglo-Saxons population within the Mexican context, to identify the relationship among: a) the components of McGregor’s XY theory; b) the different kinds of payment to people; and c) job satisfaction. For this research, we employed a survey with 51 items applied to a random sample of 233 workers in northeastern region of Mexico. Through structural equation modeling, an exploratory factor analysis (EFA) was carried out giving the constructs a reliable and valid approach. In addition, the existence of a positive relationship between theory Y and job satisfaction was found (r = 0.46). On the other hand, theory X showed no relation with any variable. Findings confirm the relevance of the strategies used by human resources departments to maintain employees’ motivation and satisfaction. Monetary retribution issues were highly valued within the Mexican work-place environment since they positively influence job satisfaction and workers’ motivation to fulfill assigned activities.